(untitled) (Bangladesh Journal of Botany, 2022)
Some growth biomarkers of germinated pea (Pisum sativum L.) using 1% yeast (Saccharomyces cerevisiae Meyen ex E.C. Hansen) extract was investigated. Seeds of pea were cultivated in the clay soil and irrigated by 1% yeast extract and/or foliar spray for 20 days. The highest values of 49 kDa apyrase, NTP, ADP substrate analysis, amino acids content, protein content and photosynthetic pigments were recorded from an addition of yeast extract to the soil along with foliar spray. NTP and ADP substrate activities analysis in the leaves were found to increase between 11.69 and 0.13%, 49 kDa gene expression between 15.77 and 0.86%, amino acids and protein contents between 40.15 and 2.85% and photosynthetic pigments between7.80 and 1.54%, when yeast extract was added to the soil or/and in the form of foliar spray then effect was more than the untreated control. Yeast extract may be used as a natural bio-fertilizer instead of harmful synthetic chemicals. Bangladesh J. Bot. 51(2): 255-262, 2022 (June)